Cap analog substrates reveal three clades of cap guanine-N2 methyltransferases with distinct methyl acceptor specificities - Benarroch, Delphine (Cold Spring Harbor Laboratory Press, 2010)
The Tgs proteins are structurally homologous AdoMet-dependent eukaryal enzymes that methylate the N2 atom of 7-methyl guanosine nucleotides. They have an imputed role in the synthesis of the 2,2,7-trimethylguanosine (TMG) RNA cap. Here we exploit a collection of cap-like substrates to probe the repertoire of three exemplary Tgs enzymes, from mammalian, protozoan, and viral sources, respectively. We find that human Tgs (hTgs1) is a bona fide TMG synthase adept at two separable transmethylation steps: (1) conversion of m(7)G to m(2,7)G, and (2) conversion of m(2,7)G to m(2,2,7)G. hTgs1 is unable to methylate G or m(2)G, signifying that both steps require an m(7)G cap. hTgs1 utilizes a broad range of m(7)G nucleotides, including mono-, di-, tri-, and tetraphosphate derivatives as well as cap dinucleotides with triphosphate or tetraphosphate bridges. In contrast, Giardia lamblia Tgs (GlaTgs2) exemplifies a different clade of guanine-N2 methyltransferase that synthesizes only a dimethylguanosine (DMG) cap structure and cannot per se convert DMG to TMG under any conditions tested. Methylation of benzyl(7)G and ethyl(7)G nucleotides by hTgs1 and GlaTgs2 underscored the importance of guanine N7 alkylation in providing a key π-cation interaction in the methyl acceptor site. Mimivirus Tgs (MimiTgs) shares with the Giardia homolog the ability to catalyze only a single round of methyl addition at guanine-N2, but is distinguished by its capacity for guanine-N2 methylation in the absence of prior N7 methylation. The relaxed cap specificity of MimiTgs is revealed at alkaline pH. Our findings highlight both stark and subtle differences in acceptor specificity and reaction outcomes among Tgs family members.